Class actions as a tool for judicial control of public policies that implement fundamental social rights (Revista do Tribunal Regional Federal da 3ª Região, 2018)
The judicial control of public policies represent an important instrument in the realization of fundamental rights. Proves to be of fundamental importance the management of collective action for this purpose, highly prominent being the establishment of standards to define its possibilities.
Keywords: judicial control of public policies; fundamental rights; class actions